Trois propositions pour changer la culture du cycliste professionnel. Une politique rénovée de prévention du dopage - Aubel , O. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2013)
With the comprehensive posture allowed by the sociology of work inspired by the "interactionnist" American sociologists, our work leads us to measure the risk of doping in professional cycling. This study is based on 48 interviews realized in six professional cycling teams and the analysis of database describing all the professional riders on the 2005-2012 period. Our research realized under the mandate of the International Cycling Union leads us to propose a new anti-doping prevention policy. The policy relies on three dimensions according to three main results of our survey. The first result is the link between the risk of doping and the level and nature of the team`s organization in rider`s supervision. The second one is relating to the performance production modality, especially the workload imposed to the riders. The third is the risk generated by precarious employment conditions in cycling teams who the economic model is particularly fragile.